Settlement of Non-Performing Financing without Collateral: An Analytical Study on Islamic Rural Banks - Riduwan Riduwan; Dwi Santosa Pambudi; Muhammad Alfian Lukluk Firdausi; Nurul Huda (Universitas Muhammadiyah Magelang, 2021)
Financing through Islamic banks carries a high risk of not being paid according to the contract's terms. As a result, Islamic banks must adhere to a stricter prudence standard. This research looks at the problem-solving model of non-collateral financing, which is influenced by both internal and external factors and carries a higher risk because the client lacks a material legal bond. The research sample consisted of 30 Indonesian Islamic Rural Banks' (BPRS) directors and commissioners. Questionnaires and in-depth interviews were used to collect data, which was then analyzed using content analysis techniques. The findings of this study show that the non-performing financing settlement model is implemented with early business assistance and then followed by financing relaxation. If no solution is found or the client declares bankruptcy, they may be released with a write-off using reserve funds from the account of writing off accounts receivable or social funds.